Socioeconomic disparities in anthropometric status among primary school children: A potential association with school meals - Mohammed Abdulrahman Alhassan; Fatima Alhasan (PLoS ONE, 2025)
Objective To assess the growth and nutritional status of children in primary schools across different socioeconomic groups in Wad-Madani City, Central Sudan, and map it to World Health Organization (WHO) standards; and to investigate a potential association between school meal intake and nutritional status. Methods This cross-sectional anthropometric study involved a randomly selected sample of 506 children from 10 primary schools in the city. Height and weight were measured following WHO standards and converted into Z-scores for weight-for-age (WAZ), height-for-age (HAZ), and BMI-for-age (BAZ). We compared the mean Z-scores between children in the private and public school sectors, adjusting for ethnicity and other potential predictors. Statistical analyses included multivariate linear regression to assess predictors of growth and nutritional status, alongside group comparisons using appropriate statistical tests. Results Children in public schools had significantly lower BAZ and HAZ levels compared to both WHO standards and private school children. The mean BAZ was -1.0 (SD =  1.23) for public school children and -0.13 (SD =  1.40) for private school children (p =  0.001), with 17.8% (n =  57) of public school children classified as thin (wasted) or severely wasted. The median HAZ was -0.20 (95% CI: -0.34, -0.02) for public school children and 0.19 (95% CI: 0.03, 0.40) for private school children (p <  0.001). Additionally, children in suburban public schools had a significantly lower mean HAZ (-0.46, SD =  11.33) compared to those in urban public schools (p =  0.009). Compared to WHO growth standards, public school children had significantly lower mean WAZ (p <  0.001), HAZ (p =  0.002), and BAZ (p <  0.001). Children who received school meals had significantly higher WAZ (mean difference =  0.619, p =  0.001), HAZ (mean difference =  0.401, p =  0.010), and BAZ (mean difference =  0.588, p =  0.003) across the entire sample. Even within the public-school subgroup, while statistical significance was not reached, all three parameters—WAZ (mean difference =  0.334, p =  0.074), HAZ (mean difference =  0.262, p =  0.123), and BAZ (mean difference =  0.299, p =  0.132)—remained consistently higher among those who received school meals. Conclusion Public school children exhibit unfavorable growth and nutritional status, which may be attributed to inadequate nutritional and calorie intake. School meals may improve nutritional outcomes. We propose urgent intervention through the provision of nutritionally adequate school meals.